Relationships between the technique index and performance in 60-m hurdle indoor races in elite male heptathletes - Kaisidou, Viktoria; Kaisidou, Leonidas; Panoutsakopoulos, Vassilios (Akademia Wychowania Fizycznego w Poznaniu)
A practical assessment of the hurdle clearance technique was carried out applying the technique index (TINDEX), namely the difference between performance in a hurdle race and performance in a respective race without hurdles. The aim of the present study was to examine TINDEX of combined events athletes that competed in all World and European Indoor Athletics Championships. The analysis included the heptathletes who won (n = 84) or did not win (n = 192) a medal, the progress of TINDEX per decade (1990s: n = 75; 2000s: n = 97; 2010s: n = 104) and its correlation with performance (total points won) in heptathlon for a total of 276 cases from the heptathlon 60-m sprint and 60-m hurdle races held from 1993 to 2019. Results revealed that medal winners (median [interquartile range] = 0.99 [0.20] s) had significantly (p < 0.001) lower TINDEX compared to nonmedal winners (1.10 [0.24] s). No significant (p > 0.05) TINDEX differences were observed among the cases in the examined decades. Finally, a significant negative correlation (τb = –0.27, p < 0.001) was observed for TINDEX and performance in heptathlon. In conclusion, hurdle clearance with the minimum time loss is a precondition for success in indoor combined events.
Keywords: sprint; track and field; performance; time analysis; heptathlon; time differential